Exploring Students Perceptions and Performance in Flipped Classroom Designed with Adaptive Learning Techniques: A Study in Distributed Systems Courses - Araújo, Pedro T.; Viana, Windson C.; Veras, Nécio L.; Farias, Eder J. P.; C. Filho, Jose Aires (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
In Computer Science, teaching Distributed Systems presents many challenges primarily related to the students' prior knowledge. Some new Learning Approaches emerged and can aid to improve learning processes in this scenario, such as Flipped Classroom and Adaptive Learning. In this context, this paper presents a study of the integration of the Flipped Classroom method with Adaptive Learning techniques for assisting Distributed Systems courses. We conducted quantitative and qualitative analysis to evaluate students' acceptance. We also implemented a quasi-experimental study to evaluate the learning impact on students. Students had a significant improvement in the test score in both approaches.